THE THE IMPACT OF EDUCATIONAL APPROACHES IN CYPRUS DURING COVID-19 RESTRICTIONS: IMPLICATIONS FOR HIGHER EDUCATION ORGANISATIONS - CHRISTODOULIDES, COSTAS (Management and Administration Journal, 2022)
COVID-19-induced restrictions on traditional classroom-based contact have posed significant challenges to academic teaching and students as well as to the management of HEIs. The new setting and extraordinary government directives culminated into threats to the quality of teaching, therefore it is important to study adaptation strategies1 in teaching and valuable lessons learned in an era when learning was substantially converted to online teaching. The main aim of this exploration study has been to identify how teaching staff adjusted teaching strategies during 2020 and what their expectations were with regards to their students’ intended learning outcomes, taking into account that learning outcomes are also related to student satisfaction. This is crucial in case COVID-19 restrictions are prolonged and online learning extended. Results from a group of 76 lecturers indicate that they have to some extent engaged in adapting conventional teaching methodologies to the new conditionalities; that for many among them, restrictions have negatively impacted quality of teaching while for a portion of lecturers the attainment of intended learning outcomes by students may have been a very difficult task. Results suggest the need to consider newer versions of teaching strategies identifying student problems; and enhancing engagement.